Umyyad Currency and the Causes which lead to coin it and Effects The expected - Sarem , Wafaa (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Currency is considered an important manifestation of the Kalifate`s or ruler`s power asit is an official source that cannot be challenged. Coins are seen as records for titles and attributes. Hence the Currency that was coined during Islam Era in Damascus, Baghdad and Cairo is considered an official document that empliticalunty of the Arab World. The plases where the currency was coined were known as Coining House ( Dar alsakka) Studying monetary is referred to as Numismatics, which is the science that studies monetary and seals. Studying Umayyad Currency through causes and effects in addition to the events between them gives a clear picture about the Islamic Civilization . Moreover, the coining prosess shows the development in various areas and it explains the political implications on the Arabs, those implications that held many positive aspects.